Respuesta :
Answer:
m = 2 or m = 0
Step-by-step explanation:
Solve for m over the real numbers:
(-5 m^2 - 8) - (-3 m^2 + m + 2) = (-5 2 m - 8) - (m - 3 2 m + 2)
(-5 m^2 - 8) - (-3 m^2 + m + 2) = -2 m^2 - m - 10 and (-5 m 2 - 8) - (m - 3 m 2 + 2) = -5 m - 10:
-2 m^2 - m - 10 = -5 m - 10
Add 5 m + 10 to both sides:
4 m - 2 m^2 = 0
Factor m and constant terms from the left hand side:
-2 m (m - 2) = 0
Divide both sides by -2:
m (m - 2) = 0
Split into two equations:
m - 2 = 0 or m = 0
Add 2 to both sides:
Answer: m = 2 or m = 0
Answer:
m = 0, 2.
Step-by-step explanation:
(-5m^2-8) -(-3m^2+m+2)=(−5m *2 −8)−(−3m* 2 +m+2)
= -5m^2 - 8 + 3m^2 - m - 2 = -10m - 8 + 6m - m - 2
= -2m^2 + 4m = 0
2m( -m + 2) = 0
m = 0, 2.